Interval multistage joint-probabilistic integer programming approach for water resources allocation and management. - Gu, J.J.; Huang, G.H.; Guo, P.; Shen, N. (Journal of Environmental Management, 2013)
In this study, an interval multistage joint-probabilistic integer programming method was developed to address certain problems in water resource regulation. This method effectively deals with data in the form of intervals and probability distribution. It can also process uncertain data in the form of joint probabilities. The proposed method can also reflect the linkage and dynamic variability between particular stages in multi-stage planning. Sensitivity analysis on moderate violations and security constraints showed that the degree of constraint violation was closely linked to the final benefits of the system. The developed method was applied in the case study of the joint-operation of the Tianzhuang and Bashan Reservoirs in Huaihe River, China. In this case study, the proposed method can deal with the water shortage problems downstream and the distribution problems caused by excess water in the reservoir. It can also guarantee the optimization of long-term water usage of both Reservoirs and the river downstream.